Coworkers can also make you sick - Costa, S.; Velez, M. J.; Lopéz, A. (16th Conference of the European Academy of Occupational Health Psychology, 2024)
Background Workplace mistreatment is a prevalent phenomenon in contemporary organizations (Dhanani et al., 2021). According to the ILO (2022) one out of five people experience some form of mistreatment at the workplace. Workplace mistreatment may assume many forms (e.g., insults, threats, bullying or physical aggression), and vary in severity, persistence, and source (Herschcovis, 2011) - such as supervisors, customers, subordinates, or coworker (Duffy et al., 2002). The current study specifically examines coworker undermining, as coworkers represent a highly significant facet of employees’ social milieu (Dutton & Ragins, 2007). Recent findings from the WBI US Survey Adults (2021) demonstrate that 21% of instances of workplace mistreatment originate from colleagues. Drawing from a conservation of resources framework and JD-R, coworker undermining can be conceptualized as a significant source of strain (Duffy et al., 2002), because employees perceive the depletion of their personal resources, both present and future (Hobfoll, 2011). However, employees’ health outcomes are influenced not only by job demands, but also by the personal resources available to employees for effectively coping with such demands. We therefore suggest that coworker undermining is positively related to somatic complaints and, that such relationship is mediated by negative emotions and moderated by forgiveness cognitions. Method Three surveys were sent to participants during a month. At time 1, 584 surveys were sent out. We received 356 usable responses (63.0% response rate). One week later, all participants received the link to survey 2, and we received 305 usable surveys (85.7% response rate). The same procedure was followed for survey 3 and the usable responses was 242 response rate was 79.3%. We then removed participants who failed the attention checks and did not complete the three surveys. Final sample was 229 employees. Results We tested our hypotheses using PROCESS macro (Hayes, 2017) models 4 (mediation) and 7 (moderated mediation). We found that coworker undermining in time 1 is related to negative affect in time 2, which in turn impacts individual’s somatic complaints in time 3. We also found that forgiveness minimizes the impact of this negative chain. In other words, individuals who forgive their colleagues do not report high levels of negative affect and somatic complaints. Moreover, we predicted that negative affect would mediate the relationship between coworker undermining and somatic complaints, conditional on different levels of forgiveness. As expected, negative affect mediated the relationship between the coworker undermining X forgiveness interaction and somatic complaints, such that coworker undermining was related to somatic complaints through an increase in negative affect, only when forgiveness was low. Conclusion The present study brings important insights for organizations and managers who want to prevent and minimize employee’s health issues. Organizations can provide training to managers about coworker relationships, specifically on how to spot problems, creating awareness and developing skills to prevent it. Organizations can also cultivate a positive environment where organizational norms capture the respect among employees. In addition, organizations can strengthen their regulations about abusive behaviors within the workplace by protecting workers from any type of aggressive behaviors.